RELASI JINN DAN AL-INS DALAM AL-QURâ€™AN: Kajian Semantik Toshihiko Izutsu - Afandi, Zamzam; Shodiq, Jaâ€™far (International Journal Ihya' 'Ulum al-Din, 2017)
The Qurâ€™an often calls the word jinn coupled with the word al-ins as Godâ€™s creatures in different forms. Based on that, the author tried to unravel the problem by studying basically the words jinn and al-ins in the Qurâ€™an and then linking both of them in Toshihiko Izutsuâ€™s semantic theory. The study begins by searching for the basic meaning and relational meaning as the foundation for finding welthansauung or worldview of the word jinn and al-ins in the Qur'an. The study found that the word jinn in the Qur'an has a closed meaning, similar to the root of majnÅ«n, jannah, and janÄ«n. Likewise, the relational meaning of the jinn described in the Qur'an both relating to the ancients before the coming of Islam, the jinns are shaitan, ifrit, angels, superhuman beings, worshiped beings, demons, and the maker of misfortune someone. As for the basic meaning of the word al-ins, the same as insÄn, basyar, the sons of adam, â€˜abd Allah, even al-ins as the representative word of man in the Qur'an can be interpreted shaitan as in surahÂ al-nÄs which states that shaitan derived from the genie and the human race. The discussion of the ontological and communicative relations between jinn and al-ins in the Qurâ€™an, it is mentioned that jinn and humans are truly Godâ€™s creatures created from different elements. These two creatures can establish communication because there is an explanation in the Qurâ€™an, as it did in the time of Adam, Sulayman and Prophet Muhammad saw.Al-Qurâ€™an kerap menyebut kata jinn bersanding dengan kata al-ins sebagai makhluk Allah yang berbeda wujud. Berangkat dari itu, peneliti mencoba mengurai permasalahannya dengan cara mengkaji secara dasar kata jinn dan al-ins dalam al-Qurâ€™an dan kemudian mengkaitkan keduannya menggunakan teori semantik Toshihiko Izutsu. Kajian dimulai dengan mencari makna dasar dan makna relasional sebagai dasar menemukan welthansauung atau pandangan dunia terhadap kata jinn dan al-ins dalam al-Qurâ€™an. Penelitian ini menemukan bahwa kata jinn dalam al-Qurâ€™an mempunyai makna tertutup, sama dengan akar kata dari majnÅ«n, jannah maupun janÄ«n. Begitu juga tentang makna relasional terhadap jin yang dijelaskan dalam al-Qurâ€™an baik yang berkaitan dengan orang-orang dahulu sebelum datangnya Islam, jin adalah syaitan, ifrit, malaikat, makhluk yang mempunyai kekuatan super, makhluk yang disembah, iblis, dan pembuat kesialan seseorang. Adapun makna dasar kata al-ins, sama seperi insÄn, basyar, bani adam, â€˜abd Allah, bahkan al-ins sebagai kata yang mewakili manusia dalam al-Qurâ€™an bisa diartikan syaitan seperti dalam suran al-nÄs yang menyatakan bahwa syaitan itu berasal dari golongan jin dan manusia. Pembahasaan tentang relasi ontologis dan komunikatif antara jinn dan al-ins dalam al-Qurâ€™an, disebutkan bahwa jin dan manusia adalah benar-benar makhluk Allah yang diciptakan dari unsur yang berbeda. Kedua makhluk ini bisa menjalin komunikasi karena ada penjelasan dalam-al-Qurâ€™an, seperti halnya yang terjadi pada zaman Nabi Adam, Nabi Sulaiman sampai Nabi Muhammad saw.